1996
DOI: 10.1002/j.1460-2075.1996.tb00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Invariant chain protects class II histocompatibility antigens from binding intact polypeptides in the endoplasmic reticulum.

Abstract: Unlike class I histocompatibility (MHC) antigens, most newly synthesized MHC class II molecules fail to be loaded with peptides in the endoplasmic reticulum (ER), binding instead to the invariant chain glycoprotein (Ii). Ii blocks the class II peptide binding groove until the class II:Ii complexes are transported to endosomes where Ii is removed by proteolysis, thus permitting loading with endosomal short peptides (approximately 12–25 amino acids). Ligands from which the groove is protected by Ii have not yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
86
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(92 citation statements)
references
References 63 publications
4
86
2
Order By: Relevance
“…Moreover, transfected cells express a substantial amount of class II molecules at their plasma membrane even in the absence of Ii (10). Such a phenotype probably results from the binding of endogenous peptides or polypeptides present in the ER (6,11) and supports the notion that occupancy of the peptide-binding groove is sufficient to allow ER egress (12).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, transfected cells express a substantial amount of class II molecules at their plasma membrane even in the absence of Ii (10). Such a phenotype probably results from the binding of endogenous peptides or polypeptides present in the ER (6,11) and supports the notion that occupancy of the peptide-binding groove is sufficient to allow ER egress (12).…”
mentioning
confidence: 72%
“…Following their synthesis, the ␣ and ␤ subunits of the class II molecule associate in the endoplasmic reticulum (ER) together with the invariant chain (Ii) (2). The latter folds in part through the groove of the class II molecule, stabilizing the ␣␤ heterodimer and preventing the undesirable binding of ER polypeptides (3)(4)(5)(6). Studies using mice with inactivated Ii genes suggested that Ii is necessary for efficient exit of newly synthesized class II molecules from the ER (7,8).…”
mentioning
confidence: 99%
“…In the absence of Ii, DR molecules may route to the endosomes via the cell surface or directly from the ER by using the DR␤ chain dileucine endosomal targeting motif (38). The ability to enter the endosomal pathway in the absence of Ii appears to be cell type specific (37,39). Two very recent in vivo studies in mice have supported the concept that altered routing of class II (38) or the absence of Ii (40) generates cell surface class II-peptide complexes that differ from those on conventional APC and alter T cell antigen-and allo-reactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Although MHCII a chains and b chains already assemble and form peptide-binding sites in the ER, they capture peptides only after arriving at the endocytic pathway. Premature peptide loading is prevented by the invariant chain (Ii, also called CD74) (Teyton et al 1990;Busch et al 1996). Ii binds the MHCII peptide-binding groove with a region in its luminal domain that is called CLIP (for class-II-associated invariant chain peptide) (Rudensky et al 1991;Chicz et al 1992;Riberdy et al 1992;Sette et al 1992;Freisewinkel et al 1993).…”
Section: Biosynthesis Of Mhciimentioning
confidence: 99%
“…Normally, Ii is synthesized in excess over MHCII, ensuring Ii rather than peptide binding to MHCII (Kvist et al 1982;Sekaly et al 1986;Marks et al 1990;Pieters et al 1991). Peptides that are transferred into the ER by TAP, for potential binding to MHCI, indeed have poor potential to bind MHCII (Bikoff et al 1993;Viville et al 1993;Elliott et al 1994;Romagnoli and Germain 1994;Busch et al 1996). Ii is encoded outside the MHC gene region, but its expression, like MHCII, is under the control of CIITA (Reith et al 2005).…”
Section: Biosynthesis Of Mhciimentioning
confidence: 99%